Comparison of Outcome of Open and Endoscopic Surgical Excision of Stage I and II Angiofibroma - Nawazish, Rida; Shamim, Syeda Hina; Saif, Mehak; Fatima, Mahnoor; Awan, Aamer Ayub; Ahmed, Maqsood (Indus Journal of Bioscience Research, 2025)
Background and aim: Juvenile nasopharyngeal angiofibroma is a highly vascular tumor in which surgical excision remains the primary treatment. Endoscopic surgery has expanded for early-stage disease, yet comparative outcomes with open techniques remain clinically relevant. This trial compared open versus endoscopic excision for Fisch stage I and II angiofibroma in terms of recurrence, operative duration, intraoperative blood loss, transfusion requirement, and hospital stay. Material and methods: A randomized controlled trial was conducted in the Department of Otolaryngology, Lahore General Hospital, Lahore, from 10 March 2025 to 20 June 2025. Sixty patients aged 10 to 25 years with Fisch stage I or II disease were randomized by lottery method to open excision (n = 30) or endoscopic excision (n = 30). Completeness of excision was assessed on postoperative magnetic resonance imaging at day 7, and recurrence was assessed at 3 months. Data were analyzed using independent t-test and Chi-square or Fisher’s exact test, with post-stratification Chi-square analysis for age, stage, and smoking status. Results: Mean age was 15.8 ± 3.3 years in the open group and 16.1 ± 3.4 years in the endoscopic group (p = 0.728). Mean operative duration was 248.6 ± 36.9 versus 156.4 ± 32.1 minutes (p < 0.001). Mean blood loss was 945 ± 310 versus 512 ± 185 mL (p < 0.001). Transfusion was required in 13 (43.3%) versus 2 (6.7%) patients (p = 0.001). Hospital stay was 5.2 ± 1.3 versus 3.4 ± 0.9 days (p < 0.001). Complete excision on day 7 magnetic resonance imaging was 27 (90.0%) versus 29 (96.7%) (p = 0.301). Recurrence at 3 months occurred in 8 (26.7%) versus 2 (6.7%) patients (p = 0.038). Conclusion: Endoscopic excision yielded superior perioperative outcomes with reduced early recurrence while maintaining comparable completeness of resection.